NS-3 Module for Machine Type Communication Device Energy Consumption - Narender Reddy Kampelli , B.N. Bhandari , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In networking research studies, NS-3 tools have emerged as a favored simulation platform among researchers. Understanding the energy usage of LTE Machine Type Communication Devices (MTCD), an LTE-M device, is essential for research in machine-type communication networks. However, NS-3 lacks a dedicated module to analyze the energy expenditure of communication between LTE and MTCDs. Scholars have previously profiled and constructed models of LTE UE energy expenditure for commercial equipment, necessitating an equivalent module within the NS-3 simulator for consistent and comparative research outcomes. In this scholarly contribution, we elucidate the conceptualization and execution of an LTE MTCD energy consumption model within the NS-3 framework. The experimental results reveal that the designed energy consumption model for LTE MTCD successfully mirrors anticipated power profiles under varied scenarios for MTCDs